Transformation of Higher Education in Uzbekistan and The Importance of Academic Independence in it - Abdurakhimova Tursunoy Abduvakhidovna (Genius Publishing Group, 2023)
This article describes the researcher's opinion on the issue of academic independence of higher education institutions in our country and the fact that it plays an important role in the transformation of higher education today, which allows to test the new model of education in practice, evaluate the existing opportunities and make future plans.
Keywords: Transformation; academic independence; Finnish education